Optical properties of La3+ NPs Ag+ co-doped zinc borotellurite glass - Faznny, Mohd Fudzi; Halimah, M. K.; Latif, A. A.; Muhammad, F. D.; Hasnimulayti, L. (Trans Tech Publications Ltd, Switzerland, 2019)
Lanthanum and silver co-doped zinc borotellurite glasses having chemical composition of [{[(TeO2)0.7(B2O3)0.3]0.7(ZnO)0.3}0.96 (La NPs)0.04]1-x(Ag2O)x with 0.02 ≤ x ≤ 0.10 molar fraction were fabricated via melt-quenching technique. X-ray diffraction (XRD) analysis confirmed the amorphous nature of the samples through the presence of broad hump instead of sharp peaks. Optical properties of the samples were determined through ultraviolet-visible spectroscopy (UVVis) in the range of 220 to 800 nm. Fundamental absorption edge observed in the optical absorption spectra shifts to longer wavelength as the concentration of silver in the glass system increases. Decreasing trend for indirect energy band gap and increasing trend of Urbach energy values with the increment of Ag content suggest the contribution of Ag to the formation of nonbridging oxygen. Enhanced optical properties of the prepared glass hints the possible application of the glass material as optical fiber in photonic field.